An estimate for the best constant in the Lp-Wirtinger inequality with weights - Raffaella Giova (Journal of Function Spaces and Applications)
We prove an estimate for the best constant C in the following Wirtinger type inequality ∫02πa|w|p≤C∫02πb|w′|p.